Plenum Series in Rehablititation and Health
DOI: 10.1007/0-306-47893-5_4
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery Framework in Rehabilitation and Mental Health

Abstract: Hutchinson, D. (Eds.) (1994). The re covery workbook: Practical coping and empowerment strategies for people with psychiatric disabilities. Boston:Center for Psychiatric Rehabilitation.Sullivan, W P (1994). A long and winding road: The process of recovery from se vere mental illness. In L. Spaniol, C. Gagne, & M. Koehler (Eds.),Psychological and social aspects of psy chiatric disability (pp. 14-24). Boston:Center for Psychiatric Rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…That is, some studies have demonstrated that autistic children and adults are perceived negatively, whereas others suggest that they are perceived positively, and still others find that perceptions vary as a function of the behavior displayed and whether they are identified as autistic. [4][5][6][7][8][9] Most studies have relied on a single methodology, namely explicit selfreport measures.…”
Section: Implicit and Explicit Attitudes Toward Autistic Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, some studies have demonstrated that autistic children and adults are perceived negatively, whereas others suggest that they are perceived positively, and still others find that perceptions vary as a function of the behavior displayed and whether they are identified as autistic. [4][5][6][7][8][9] Most studies have relied on a single methodology, namely explicit selfreport measures.…”
Section: Implicit and Explicit Attitudes Toward Autistic Adultsmentioning
confidence: 99%
“…4,5 Health care professionals similarly have negative perceptions about children with developmental disorders such as the perception that they are unintelligent. 9 Neurotypical adults perceive autistic children more negatively, ascribing traits such as ''awkward'' to them. 7 In addition, neurotypical adults and adolescents per-ceive autistic adults more negatively (e.g., more awkward, less likeable) than neurotypical adults, have misconceptions about autism, and are less willing to engage with autistic adults during a first meeting than neurotypical adults.…”
Section: Implicit and Explicit Attitudes Toward Autistic Adultsmentioning
confidence: 99%
“…Such social consequences are known to be related to poor health outcomes [11] and may ultimately create a barrier in the path to recovery (e.g. [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that people with intellectual disabilities or other developmental disorders experience stigmatized treatment by frontline workers (Wahl & Harman 1989; Spaniol et al. 2003; Cooney et al.…”
Section: Introductionmentioning
confidence: 99%